A Comparative Study of the Four Imams and Imam Ibn e Hazm on Qiyas: ائمہ اربعہ ؒ اور امام ابن حزم ؒ کا قیاس سے متعلق تقابلی مطالعہ - Ahmad, Zishan; Muqadusullah, Dr. (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Islam is a comprehensive and complete code of life, all issues of life are in the grip of its teachings, and however the rules of Islam are of two kinds. Specified ((منصوص: The clear solution of which is contained in the Book of Allah and the Sunnah of the Prophet. Unspecified (غیر منصوص): The clear solution of which is not found in the Book of Allah and the Sunnah of the Prophet. That is, an issue which is not explicitly mentioned in the Book of Allah and the Sunnah of the Prophet (peace and blessings of Allah be upon him) and no consensus has been reached in this regard. Qiyas is one of the most important and basic sources of Shari’ah. The Holy Prophet (PBUH) and his Companions used to deduce the rules through Qiyas. Except for the Ahl al-Zawahir and some Mu’tazilites, no one has denied the validity of the Qiyas. The four Imams count Qiyas among the sources of Shari’ah. They prove the validity of Qiyas by testifying from the Book of Allah and the Sunnah of the Prophet and the sayings of the Companions. While Allama Ibn Hazm has denied the Qiyas. Imam Ibn Hazm has strongly expressed his position on the invalidation of Qiyas. He says that it is not permissible in religion to take Qiyas from speculation and opinion. In the event of a dispute, Allah has commanded that the matter be referred to the Book of Allah and the Messenger of Allah (peace and blessings of Allah be upon him). Now, whoever returns the disputed matter to speculation or opinion, he has violated the command of God, which is a condition of Iman. Qiyas is a name about which Allah Almighty has not given any permission and has not revealed any evidence in this regard. Undoubtedly, Qiyas is just a guess. What Allah has commanded is obligatory and what He has forbidden is haram. What He has neither commanded nor forbidden is permissible and lawful. There is no need for Qiyas or opinion on anything now. He who made obligatory the thing for which the text was not obligatory or declared the thing which is not haram as haram, then he invented a new law in the religion which was not commanded by Allah.